Alpha–conotoxin, omega–conotoxin and mu–conotoxin time–resolved absorption and resonance FT–IR and Raman biospectroscopy and density functional theory (DFT) investigation of vibronic–mode coupling structure in vibrational spectra analysis - Heidari, Alireza; Esposito, Jennifer; Caissutti, Angela (International Journal of Advanced Chemistry, 2019)
A Conotoxin is one of a group of neurotoxic peptides isolated from the venom of the marine cone snail, genus Conus. Conotoxins, which are peptides consisting of 10 to 30 amino acid residues, typically have one or more disulfide bonds. Conotoxins have a variety of mechanisms of actions, most of which have not been determined. However, it appears that many of these peptides modulate the activity of ion channels. Over the last few decades Conotoxins have been the subject of pharmacological interest. Parameters such as FTÂâ€“IR and Raman vibrational wavelengths and intensities for single crystal Alphaâ€“Conotoxin, Omegaâ€“Conotoxin and Muâ€“Conotoxin are calculated using density functional theory and were compared with empirical results. The investigation about vibrational spectrum of cycle dimers in crystal with carboxyl groups from each molecule of acid was shown that it leads to create Hydrogen bounds for adjacent molecules. The current study aimed to investigate the possibility of simulating the empirical values. Analysis of vibrational spectrum of Alphaâ€“Conotoxin, Omegaâ€“Conotoxin and Muâ€“Conotoxin is performed based on theoretical simulation and FTâ€“IR empirical spectrum and Raman empirical spectrum using density functional theory in levels of F/6â€“31G*, HF/6â€“31++G**, MP2/6â€“31G, MP2/6â€“31++G**, BLYP/6â€“31G, BLYP/6â€“31++G**, B3LYP/6â€“31G and B3LYP6â€“31â€“HEG**. Vibration modes of methylene, carboxyl acid and phenyl cycle are separately investigated. The obtained values confirm high accuracy and validity of results obtained from calculations.Â